A single computational model to simulate the three foot-rocker mechanisms of the gait cycle - Nicolás Yanguma-Muñoz; Javier Bayod; Christian Cifuentes-De la Portilla (Scientific Reports)
Abstract The use of computational models of the human foot based on finite element analysis offers a promising alternative for understanding the biomechanical internal changes of this structure. However, the evaluation of dynamic scenarios has been challenging. This research aims to design a computational model that accurately simulates foot biomechanics during the stance period of the gait cycle in healthy and flatfoot scenarios. The model is focused on analyzing stress variations in soft tissues such as the plantar fascia and spring ligament to provide valuable insights into the internal biomechanics of the foot. The results were evaluated using maximum principal stress. Validation was performed by measuring clinical angles and comparing the range of motion of foot joints with known values for each phase. Results show that the plantar fascia and spring ligament stress increase during the second and third rockers compared to the first rocker. Additionally, as was expected, flatfoot simulations show stress increments in those evaluated soft tissues, while surgical treatment scenarios contributed to stress reduction in these regions. These findings emphasize the active role of the plantar fascia and spring ligament, particularly during approximately 50% of the stance period when the plantar arch deformity is greater. Results show valuable insights into the internal biomechanics of the foot through computational models.